Age effect analysis of different gender groups in spatial ability test based on virtual reality technology - Guo, Yangyang; Zhang, Mengdi; Gu, Jiangpeng; Liu, Qiyang; Liu, Xinyang; Wang, Jie; Ma, Fangfang; Zhai, Lihong; Qi, Jianlin; Jin, Zhanguo (Frontiers in Psychology, 2025)
PurposeThe objective of the present study was to examine the impact of age and cognitive autonomy across various gender categories. Moreover, this research seeks to delve into the dissociation of diverse spatial aptitude assessments, with the aim of elucidating the intricate mechanism underpinning spatial capability.MethodBased on virtual reality technology, this study conducted spatial ability tests on 312 volunteers, aged from 18 to 90 years old, including R-letter rotation test, S-M mental rotation, surface development test and maze test.ResultsThe analysis revealed that the spatial ability of men decreases with age, but the spatial ability of women between 28 and 37 years old is better than that of other age groups. Males outperformed females in most visual ability tests, but there was no significant difference in some age groups. There was no significant correlation between the R-letter rotation test and the S-M mental rotation test, and the two tests were independent. The relationship between visual ability and orientation ability is different in different spatial test indicators.ConclusionThis investigation further elucidates the dissimilarities in the age-related characteristics of spatial aptitude among diverse gender cohorts, as well as the autonomy of various spatial aptitude assessments. Such distinctions are instrumental in occupational preference for disparate groups, calling for comprehensive and meticulous inquiries into the maturation of spatial proficiency by researchers.